Fish downstream passage over weirs at low-head hydropower plants: Field study of total dissolved gas concentrations - Süss, Gabor; id_orcid:0 009-0001-9905-2139; Albayrak, Ismail; id_orcid:0 000-0002-4613-6726; Evers, Frederic M.; id_orcid:0 000-0001-5181-8978; Boes, Robert; id_orcid:0 000-0002-0319-976X (ETH Zurich, 2024)
Hydropower plants (HPPs) and other barriers interrupt the longitudinal connectivity in river networks, which hinders or delays fish migration. One potential solution for downstream fish passage is to use conventional spillways and weirs, e.g., in periods of pronounced fish downstream migration. However, the knowledge of fish injury and mortality during weir/spillway passage as well as on the hydraulic conditions in the associated stilling basins is limited. In particular, it has been rarely studied for European fish species. Weir overflow leads to the entrainment of air, which dissolves in water under pressure. Excessive Total Dissolved Gas (TDG) saturations can lead to gas bubble disease in fish, which can potentially cause fish injuries and mortality. Therefore, in this study we investigate the safety of fish passage over weirs in terms of characteristic hydraulic parameters at the case study low-head HPP Bannwil on the Aare River in Switzerland. To this end, TDG saturations and flow velocities were measured and mapped in the flow reach upstream of the weir and powerhouse and from the stilling basin to 500 m downstream of the power plant. The measurements were conducted using a remote-controlled Teledyne Marine Q-Boat equipped with a River Pro 1200 kHz Acoustic Doppler Current Profiler (ADCP), a Tal-Tech Barotrauma Detection System (BDS) with multiple pressure sensors and a Pro-Oceanus Solu-Blu TDG probe. Compared to the upstream flow reach, the TDG saturation was higher both at the end of the stilling basin and in the turbine outlets. At the downstream end of the study area, 500 m downstream of the weir, the water was still supersaturated. However, compared to thresholds reported in literature, the measured uncompensated TDG saturations were non-critical for juvenile Atlantic salmon (Salmo salar), a target fish species in the Aare River. More measurements at higher discharges and at weirs/spillways with different heads are recommended for follow-up studies because Atlantic Salmon, which are expected to come ...